EFFICACY OF INTRA-ARTICULAR KETOROLAC AND LIGNOCAINE ON POST-OPERATIVE PAIN RELIEF AFTER ARTHROSCOPIC KNEE SURGERY - Niazi, Auon Shabbir Khan; Bajwa, Mubashar Ahmed; Zahra, Midhat; Niazi, Muhammad Uzair Khan; Zainab, Irta; Anwer, Adnan (Journal of Ayub Medical College Abbottabad, 2022)
Background: Arthroscopy of the knee is preferably done under spinal anaesthesia. The optimal analgesia for effective postoperative pain control is important to permit early discharge, comfort and mobility of the patient. Objective of the study is to assess the efficacy of ketorolac and lignocaine administered intra-articularly for postoperative pain following knee arthroscopic surgery. Methods: A total of 133 patients were randomized into two groups with one group receiving intra-articular Ketorolac and the other group receiving intra-articular Lignocaine. Postoperative pain was then assessed using the Visual Analog Scale (VAS) at 4, 8, 12 and 24 hours after surgery. Result: Both the groups had effective analgesia at 4 hours. The best analgesia was seen in the group that received Ketorolac Intra-articularly and it was found statistically significant. Conclusion: Administration of intra-articular Ketorolac injection is safe and effective way of achieving postoperative pain relief after arthroscopic knee surgery.